Village Funds Supervision by the Village Consultative Body (BPD) in Batumatoru Village, Lariang District, Pasangkayu Regency - Zulkifli Zulkifli; Suasa Suasa; Mukarramah Mukarramah; Daswati Daswati; Muhammad Ahsan Samad (Universitas Negeri Makassar, 2018)
Village funds are a form of assistance from the government as a means of supporting and stimulating development and community empowerment in the village. The purpose of this study was to determine the supervision of village funds by the village consultative body in Batumatoru village, Lariang district, Pasangkayu Regency. The research method used is a qualitative research method by adopting escort theory. According to Sondang P Siagian there are two indicators of supervision namely direct supervision and indirect supervision. Data collection techniques are carried out through field research which includes observation, interviews and documentation. Analysis of the data used is data reduction, data presentation, and data verification. By using a purposive technique with a total of 7 informants. The results showed that the implementation of supervision of village funds in Batumatoru Village was still not optimal. Due to lack of supervision in the implementation of the use of village funds, both directly and indirectly. This was heard by complaints from the public regarding the government's performance in implementing the use of village funds.